Limited treatment adaptation despite poor asthma control in asthma patients treated with inhaled corticosteroids. (2nd January 2016) - Roche, Nicolas; Pribil, Céline; Devillier, Philippe; Van Ganse, Eric; Schück, Stéphane; Doussaint, Johanna; Martin, Jennifer; Nachbaur, Gaëlle; Boucot, Isabelle
Abstract: Objective : Current asthma guidelines recommend use of inhaled corticosteroids (ICS) in patients with persistent disease. This study was designed to investigate (1) the proportion of patients prescribed ICS-containing maintenance treatment who achieve asthma control, (2) determinants of control and (3) how physicians adapt treatment to the level of control. Methods : General practitioners (GPs) and chest physicians (CPs) in France recruited patients consulting for asthma and prescribed an ICS. Over a 2-year follow-up period, asthma symptoms in the previous 3 months and treatments prescribed were documented at each visit. Variables independently associated with asthma control were determined by multiple logistic regression. Results : Data were available for 924 patients recruited by GPs and 455 recruited by CPs. Asthma control was acceptable in only 24% of patients at inclusion, and in 33.6% at the last follow-up visit. Five factors were independently associated with asthma control: age (or time since diagnosis), gender, smoking status, allergic aetiology of asthma and treatment. Most patients (56.3%) were prescribed the same ICS dose regimen at the end of follow-up as at inclusion. The intensity of controller therapy had been increased in only 12.2% of patients unacceptably controlled at inclusion. Conclusions : Asthma was unacceptably controlled in most patients receiving ICS-containing maintenance treatment and remained so during follow-up. Despite this, treatment adaptations by GPs and CPs were very infrequent. This unsatisfactory situation may be improved by adopting a more dynamic approach to tailoring controller therapy to the needs of the patient.